1986
DOI: 10.3109/03009748609098208
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Evaluation of the Effects of Ultrasonic and Ultraviolet irradiation on Tissue Regeneration

Abstract: Twenty rabbits were divided into two matching groups. Holes of 1 cm2 area were bored through the full thickness of the pinna of both ears in each rabbit. In group I, the right ears were irradiated with pulsed ultrasound three times/week for 18 weeks. In group II, the right ears were irradiated with ultraviolet rays using a hot quartz lamp, three times/week for 18 weeks. The left ears in all rabbits were not irradiated and acted as controls. The rate of wound healing was calculated in terms of decrease in surfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

1997
1997
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 1 publication
0
7
0
1
Order By: Relevance
“…1D, arrow). In a number of studies, it has been established that ultrasound intensities from 0.1 to 0.5 W/cm 2 accelerate the repair phase in wounded tissues (Young and Dyson, 1990;Taskan et al, 1997;El-Batouty et al, 1986). 1E).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1D, arrow). In a number of studies, it has been established that ultrasound intensities from 0.1 to 0.5 W/cm 2 accelerate the repair phase in wounded tissues (Young and Dyson, 1990;Taskan et al, 1997;El-Batouty et al, 1986). 1E).…”
Section: Resultsmentioning
confidence: 99%
“…The data demonstrate that L929 cell cultures submitted to low-intensity ultrasonic irradiation (0.2e0.6 W/ cm 2 ) maintained shape and cellular integrity, thereby corroborating the results of Hsieh (2006). In a number of studies, it has been established that ultrasound intensities from 0.1 to 0.5 W/cm 2 accelerate the repair phase in wounded tissues (Young and Dyson, 1990;Taskan et al, 1997;El-Batouty et al, 1986).…”
Section: Resultsmentioning
confidence: 99%
“…In some animal studies, researchers found that ultrasound at the intensities of 0.1 W/cm 2 and 0.5 W/cm 2 accelerates the inflammatory phase of repair [6,9,35]. This reported accelerated repair agrees with the findings from several other suggestions that low-dose ultrasound of approximately 0.5 W/cm 2 pulsed with a frequency of 1 or 3 MHz promotes wound healing [34][35][36][37]. Our treatment protocol included pulsed ultrasound with a dose of 0.5 W/cm 2 at a frequency of 1 MHz for 5 days in the ultrasound group, a protocol that was applied in most studies.…”
Section: Discussionmentioning
confidence: 99%
“…[38][39][40][41][42] In addition, collagen deposited after US treatment is stronger and better organized. [39][40][41][42][43][44] Not surprisingly, tissue treated with US progresses through the phases of healing more rapidly. 39 Chemical mediators produced after US treatments include tissue growth factors, which, in turn, mediate the activation of intracellular signaling pathways.…”
Section: Physical Therapymentioning
confidence: 98%